Uncertain reflective functioning, anxious attachment, and cumulative impact of early relational trauma as predictors of severity in borderline personality disorder - K Dharani Devi; Poornima Bhola; Prabha S. Chandra (Industrial Psychiatry Journal)
Background: The mentalization model of borderline personality disorder (BPD) utilizes a developmental psychopathology lens, emphasizing an unstable or reduced capacity to mentalize—stemming from early attachment disruptions and relational trauma—as the core feature of BPD. While the empirical evidence for the proposed intersections between mentalizing, attachment, and trauma and the development and manifestations of borderline personality is still limited, this knowledge is essential for developing effective assessments and interventions. Aim: To examine mentalizing, attachment, and early relational trauma as predictors of the severity of symptoms in BPD. Materials and Methods: The sample included 60 individuals diagnosed with BPD, aged 18–45 years, recruited from inpatient and outpatient services in a tertiary care mental health center. Participants completed measures of mentalizing (Reflective Functioning Questionnaire, Interpersonal Reactivity Index, and Reading the Mind in the Eyes test), attachment (Attachment Style Questionnaire), early relational trauma (Complex Trauma Questionnaire), and symptom severity (Borderline Symptom List). Results: The majority of the participants reported experiences of polyvictimization (93.3%) with the most common traumas being psychological abuse (93.3%), neglect (91.7%), and rejection (90.0%). Regression analyses revealed that uncertain reflective functioning, anxious attachment style, and the cumulative impact of trauma together predicted 53.1% of the variance in BPD symptom severity. Conclusion: Impaired mentalizing, characterized by inflexible understanding of mental states, is a critical target for therapeutic interventions in BPD. The significant role of anxious attachment and the necessity of assessing the perceived impact of traumatic experiences highlight the importance of trauma-informed and mentalization-based interventions for this vulnerable group.